The Effect Of The Use Of Learning Media And Teachers' Teaching Styles On Student Learning Outcomes At The Elementary Education Level - Iqlima Sari; Apdoludin (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, Jurusan Tarbiyah dan Keguruan, Sekolah Tinggi Agama Islam Negeri Majene, 2025)
This study aims to find out and analyze the influence of the use of learning models and teachers' teaching styles on student learning outcomes at SDN 060/II Muara Bungo. This study uses an explanatory quantitative approach with a survey method to test the influence of learning models and teachers' teaching styles on student learning outcomes at SDN 060/II Muara Bungo. Data was collected through Likert scale questionnaires, documentation of final exam scores for the even semester of the 2024/2025 school year, and limited observations as supporting data. All data were analyzed using multiple linear regression after first going through validity, reliability, and classical assumption tests to ensure the feasibility of statistical analysis, so that the results of the study could be interpreted objectively, accurately, and scientifically accountable. The results of the study show that the learning model and teacher's teaching style have a significant effect on student learning outcomes at SDN 060/II Muara Bungo, where the use of varied learning models and teaching styles that are communicative and in accordance with the characteristics of students are able to increase learning achievement optimally. These findings confirm that the quality of the learning process is highly determined by the ability of teachers to manage learning in an innovative, interactive, and democratic manner, so that the development of teachers' pedagogic competencies is a strategic step in an effort to improve student learning outcomes.